Formulation and characterization of cholesterol-based nanoparticles of gabapentin protecting from retinal injury - Mokhtar, Hatem I.; Khodeer, Dina M.; Alzahrani, Sharifa; Qushawy, Mona; Alshaman, Reem; Elsherbiny, Nehal M.; Ahmed, Esam Sayed; Abu El Wafa, Esam Ghanem; El-Kherbetawy, Mohamed K.; Gardouh, Ahmed R.; Zaitone, Sawsan A. (Frontiers in Chemistry, 2024)
Introduction This study aimed to prepare cholesterol and stearic acid-based solid lipid nanoparticles of gabapentin (GAB-SLNs) for protection against streptozotocin (STZ)-induced retinal injury in rats. Methods We prepared four preparations of GAB-SLNs using a hot high-shear homogenization ultrasonication process, and the best formulation was selected and tested for biological activity. The retinal injury was brought in male adult albino rats while gabapentin doses continued for 6 weeks. Six groups of rats were assigned as the vehicle, diabetic, diabetic + gabapentin (10–20 mg/kg), and diabetic + GAB-SLNs (10–20 mg/kg). GAB-SLN#2 was selected as the optimized formulation with high entrapment efficacy (EE%, 98.64% ± 1.97%), small particle size (185.65 ± 2.41 nm), high negative Zeta potential (−32.18 ± 0.98 mV), low polydispersity index (0.28 ± 0.02), and elevated drug release (99.27% ± 3.48%). The TEM image of GAB-SLN#2 revealed a smooth surface with a spherical shape. Results GAB-SLNs provided greater protection against retinal injury than free gabapentin as indicated by the histopathology data which demonstrated more organization of retinal layers and less degeneration in ganglion cell layer in rats treated with GAB-SLN#2. Further, GAB-SLN#2 reduced the inflammatory proteins (IL-6/JAK2/STAT3) and vascular endothelial growth factor (VEGF). Conclusion The preparation of GAB-SLNs enhanced the physical properties of gabapentin and improved its biological activity as a neuroprotectant. Further studies are warranted to validate this technique for the use of oral gabapentin in other neurological disorders.